Comparative Study of Adverse Childhood Experiences of Adolescents in Indonesia - Ristyanda, Thifal Augista; Wicaksana, Bintang Sasmita; Syakarofath, Nandy Agustin (Universitas Islam Indonesia, 2024)
Adolescence is a transitional period from childhood to adulthood. The global adolescent population currently exceeds 1.2 billion, making up 16% of the world’s population. Adverse childhood experiences in adolescents contribute significantly to mental health issues and also have an impact on adult lives. These experiences can be influenced by various factors including demographic background. Therefore, this study aimed to determine the differences in adverse childhood experiences with demographic background in adolescents in Indonesia. A comparative quantitative method with subjects aged 12-21 was adopted in this study. Furthermore, the instrument used was the World Health Organization Adverse Childhood Experiences Questionnaire (WHO ACE-IQ) which was further analyzed using the Jamovi 2.3.21 program. The results showed that 65.3% of the subjects experienced multiple adversities dominated by adolescent girls. Additionally, the dimension of adverse childhood experiences was the highest in emotional neglect. Other results showed that there was a significant role of demographic background including age with the highest prevalence in late adolescence (18-21 years) and parental marital status with the largest group of divorce in adverse childhood experiences. Future studies were further expected to examine and conduct publications with an equal number of subjects in each province throughout Indonesia to calculate prevalence more accurately and explore the relationship betweendemographic background and adverse childhood experiences. In this context, the study provided implications for adolescents to possess an overview of adverse childhood experiences.